Heptageniidae (Insecta, Ephemeroptera) of Thailand - Boonsoong, Boonsatien (Pensoft Publishers, 2013)
Abstract. Nine genera and twenty-two species of heptageniid mayflies from Thailand are defined in this present work as well as one suggested further subgenus, Compsoneuria (Siamoneuria) kovaci (species “incertae sedis”) including some particular characters. Taxonomic remarks, diagnoses, line drawings of key characters, distribution, habitat and biological data, and a larval key to the genera and species are provided. The chorionic eggs of eight genera and eight species were observed and shown using a scanning electron microscope.